Effects of a Single Session of Whole-Body Vibration Exercise on Haematological and Biochemical Parameters, and Serum Cortisol Levels in Cats - Blazizza, M. F.S. [UNESP]; Rahal, S. C. [UNESP]; Santos, I. F.C. [UNESP]; Silva, B. M. [UNESP]; Ferreira, G. M. [UNESP]; Oba, E. [UNESP]; Tsunemi, M. H. [UNESP]; Takahira, R. K. [UNESP] (Brill Academic Publishers, 2021)
Dra. Aurora García-González The aim of this study was to evaluate the effects of a single-session of whole-body vibration (WBV) exercise on haematological and serum biochemical parameters and serum cortisol levels in healthy adult cats. Ten healthy neutered crossbred cats, five males and five females, aged 2 to 4 years and weighing 3.25-5.15 kg, were enrolled. All cats were tested in the same period starting at 12:00 a.m. and under same environmental conditions. A 1 h period of acclimatisation and rest was completed prior to the WBV session. During the WBV session, the cat was placed in a standing position on the centre of the vibrating platform. Each cat was exposed to a single WBV session. The protocol was 30 Hz for 5 min, followed by 50 Hz for 5 min and finishing with 30 Hz for 5 min. The peak displacements were 3.10 mm and 3.98 mm and the peak accelerations 55.0 m/s and 195.96 m/s. Complete blood cell count, serum biochemistry (alanine aminotransferase, creatinine, creatine phosphokinase) and serum cortisol were determined at three time-points: before (T0), immediately after (T1), and at 4 h after the end of the WBV session (T2). Immediately after increasing the frequency from 30 to 50 Hz, two cats (20%) tried to sit and showed signs of agitation that ceased after 15 s. No cat tried to jump out. The variables presented no statistically significant differences among the time-points. In conclusion, a 15 min session of WBV exercise at frequencies of 30, 50 and 30 Hz does not cause significant changes in haematological or serum biochemical parameters, nor in serum cortisol levels in healthy adult cats.
Keywords: exercise; feline; platform; vibration